TEKNIK PEMERIKSAAN USG GINJAL PADA KLINIS HYDRONEPHROSIS : STUDI KASUS - Gando Sari; Nursama Heru; Darusalam (JRI (Jurnal Radiografer Indonesia), 2018)
ABSTRACT Hydronephrosis is a renal swelling due to urine buildup. Symptom of hydronephrosis is according to acute or chronis blockage, partly or all of renal, happened unilateral or bilateral. Blockage happened on urethra causes of illness from uretha distention. Urine can not flow by normally as usually as make new infection which could be stone renal and bleeding on urine. If blockage happened, it causes of failure renal. To evalution hydronephrosis can do by ultrasonografi examination. Keywords : Hydronephrosis, ultrasonografi (USG), renal, uretha.